Pengaruh Role Stress Dan Self Efficacy Terhadap Kinerja Auditor Dengan Emotional Quotient Sebagai Variabel Moderating(Studi Empiris pada Kantor Akuntan Publik di Surakarta dan Yogyakarta) - Mustofifi, Ummul Banin, Dr. Zulfikar, SE., M.Si (2017)
This study aimed to determine the effect of role stress and self efficacy on the performance of the auditors using the emotional quotient as a moderating variable. The population in this study were all auditors who worked in the public accounting firm in Surakarta and Yogyakarta. The method used to obtain samples was a convenience sampling technique. Samples in total, there were 35 respondents in this study. Data was analyzed with multiple linear regression analysis and Moderated Regression Analysis (MRA). The result showed that R2 was 0.732 which meant 73.2% of the performance of auditors could be explained by role conflict, role ambiguity, self-efficacy and emotional quotient variables. The remaining value (26.8%) was explained by other variables besides the researched model. The result of the T test also showed that role conflict and self efficacy affected the performance of auditors. Role ambiguity and emotional quotient did not affect the performance of auditors. The interaction of role conflict and emotional quotient affected the performance of auditors. The interaction of self efficacy and emotional quotient affected the performance of auditors. While the interaction of role ambiguity and emotional quotient did not affect the performance of auditors.